Deviant Marriage Practices in Lolo Hilir Village According To The Marriage Law and Islamic Law - Pirman, Riko; Hariyadi, Riski (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This paper discusses the basis of the Lolo Hilir community who must comply with the orders of the marriage law as a means of addressing marriage issues in the modern era. This research includes field research, which is Descriptive-Analytical in nature, using a sociological-normative approach. The results showed that the UUP must be obeyed by the Indonesian people, especially the village of Lolo Hilir by looking at the basis of the obligation in Article 27 paragraph (1) of the 1945 Constitution in positive Indonesian law and in Islamic law also regulated in QS. An-Nisa': 59 and 83. According to Muhammad Abduh, the result of thinking in this law is ijmâ', the third source of Islamic law, which occurs because there is no definite nash or proposition regarding the problems that occur in this modern era and the law was formed by many experts including scholars, jurists, women experts and including the community, it must be obeyed for the benefit and peace so that there is a sense of security and tranquility in carrying out daily life in the community of Lolo Hilir village.